EMPOWERING COMMUNITIES THROUGH THE 'BANYU BIRU ANDARU' CLEAN WATER EMPOWERMENT PROGRAM: A CASE STUDY OF PT BORNEO INDOBARA'S INITIATIVE IN ANGSANA SUB-DISTRICT, TANAH BUMBU - Dindin Makinudin; Silvyna Aditia; Bilqis Nabila; Muhammad Rifqi Zakaria (Jurnal Abdimas Bina Bangsa, 2024)
This qualitative descriptive study provides a comprehensive examination of the effects of PT Borneo Indobara's Corporate Social Responsibility (CSR) initiative, "Banyu Biru Andaru," on enhancing clean water access and fostering community well-being within the villages of Banjarsari and Mekarjaya. Employing a methodological approach centered on document analysis through extensive literature review, the research delves into third-party evaluation reports and internal data extracted from annual reports, shedding light on the multifaceted impact of the program. Noteworthy findings reveal significant strides in addressing the critical issue of clean water scarcity through the implementation of various sub-programs, alongside the introduction of an innovative business model aimed at empowering communities to independently manage water resources. Furthermore, the program emerges as a driving force for social transformation, aligning with Sustainable Development Goal 6 and catalyzing shifts in societal dynamics. Notably, the calculated Social Return on Investment (SROI) value of 3.10 underscores the tangible benefits generated by the initiative, including reduced household expenditures and enhanced environmental sustainability, reflecting the substantial returns on investment and the commitment towards sustainable clean water solutions